2006
DOI: 10.1158/1535-7163.mct-05-0117
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase inhibitors in urinary bladder cancer:in vitroandin vivoeffects

Abstract: More than 14,000 people die from invasive transitional cell carcinoma (TCC) of the urinary bladder yearly in the United States. Cyclooxygenase (COX)-inhibiting drugs are emerging as potential antitumor agents in TCC. The optimal in vitro or in vivo systems to investigate COX inhibitor antitumor effects have not been defined. The purpose of this study was to determine COX-1 and COX-2 expression and antitumor effects of COX inhibitors in human TCC cell lines (HT1376, RT4, and UMUC3 cells) and xenografts derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 24 publications
2
42
0
1
Order By: Relevance
“…Therefore, we focused on a selective COX-2 inhibitor celecoxib used for the treatment of several diseases. It has also been reported that celecoxib inhibited the cell growth of high-grade bladder cancer in vitro and in vivo (5), and that celecoxib could induce apoptosis in various cancer cells independent of COX-2 inhibitory activity (6). However, the underlying mechanisms still remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we focused on a selective COX-2 inhibitor celecoxib used for the treatment of several diseases. It has also been reported that celecoxib inhibited the cell growth of high-grade bladder cancer in vitro and in vivo (5), and that celecoxib could induce apoptosis in various cancer cells independent of COX-2 inhibitory activity (6). However, the underlying mechanisms still remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…14 Prostaglandins, produced by COX-2 activity, increase cell proliferation; inhibit apoptosis; promote angiogenesis; alter cellular adhesion, which allows for metastasis; inhibit immune surveillance; and may activate xenobiotics to reactive substances that are carcinogenic. 16 In human patients, recent studies found that COX-2 is upregulated in precancerous skin lesions, such as actinic keratosis and squamous-cell carcinoma (SCC). 3,12,19 In dogs, COX-2 was strongly expressed in neoplastic keratinocytes in all cases of SCC of the skin.…”
mentioning
confidence: 99%
“…In addition, there is data indicating that the potentiation of gemcitabine effects seen in preclinical models of pancreatic cancer is mediated through modulation of other targets, such as nuclear factornB activation, which may contribute to the induction of apoptosis (43). There is evidence in models other than the pancreas that achieving efficacious drug concentrations is a problem with celecoxib and other COX inhibitors (44). To improve the bioavailability and decrease the systemic effects of celecoxib, alternative delivering strategies, such as chitosan-based, biodegradable slow-releasing platforms, (46).…”
Section: Discussionmentioning
confidence: 99%